2011
DOI: 10.1007/s00404-011-2116-2
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and perioperative outcomes in endometrial cancer surgery

Abstract: Obesity increases surgical blood loss and operative time. However, obesity does not affect length of hospital stay, number of lymph nodes harvested, or perioperative complications in uterine cancer staging surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
22
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 25 publications
5
22
0
Order By: Relevance
“…This difference was significant in three studies. 23,24,28 It was also significant in four studies that compared laparotomy versus minimally invasive surgeries. 15,25,26,29 Mean ORT ranged from 98 to 237 minutes in nonobese women and from 108 to 270 in obese and morbidly obese patients.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…This difference was significant in three studies. 23,24,28 It was also significant in four studies that compared laparotomy versus minimally invasive surgeries. 15,25,26,29 Mean ORT ranged from 98 to 237 minutes in nonobese women and from 108 to 270 in obese and morbidly obese patients.…”
Section: Discussionmentioning
confidence: 91%
“…There were ten retrospective studies, 3,4,7,15,[22][23][24][25][26][27] three prospective studies, [28][29][30] and no randomized clinical trials (RCTs) in this review. The sample size of the retrospective studies and prospective studies ranged between 42 and 655 women and 86 and 233 women, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Obesity has been linked to poorer surgical outcomes, including longer operative times and increased postoperative complications, particularly wound infections. 4,5 Historically, hysterectomies and other major gynecological procedures were performed via laparotomy. As technology advanced, many gynecologists have transitioned to minimally invasive surgical techniques such as traditional laparoscopy and robotic-assisted surgery.…”
mentioning
confidence: 99%
“…The only difference found was in longer operative time and lower incidence of both ileus and wound hematomas in obese patients. Even more compelling is the paper by Santoso et al [14] demonstrating analogous outcome profile in obese patients undergoing endometrial cancer staging, an arguably more extensive procedure. Although a large Danish cohort study suggested that obesity is associated with a higher risk of infectious and all bleeding complications after abdominal hysterectomy increase in the risk of the latter was also found in women with BMI lower than 20 kg/m 2 [15].…”
Section: Discussionmentioning
confidence: 94%